Architecture 1980 : The Presence of the Past - Venice Biennale. - Battisti, Emilio; Brusatin, Manlio; Cellini, Francesco; D'Amato, Claudio; Farina, Paolo; Galasso, Giuseppe; Jencks, Charles; Norberg-Schulz, Christian; Portoghesi, Paolo; Scully, Vincent; Battisti, Emilio; Brusatin, Manlio; et al. (New York : Rizzoli International Publications, 1980)
Anselmi, Alessandro ; Architektengroep VDL ; Batey, Andrew ; Beeby, Thomas Hall ; Benamo, Georgia ; Biurrun Salanueva, Francisco ; Bigelman, David ; Blatteau, John ; Bofill, Ricardo ; Bonet, Pep ; Brusatin, Manlio ; Buffi, Jean-Pierre ; Cellini, Francesco ; Chiatante, Paola ; Cirici, Christian ; Clotet, Lluis ; Coenen, Jo ; Cohen, Stuart ; Colucci, Gabriella ; Consuegra, Guillermo Vazquez ; Cosentino, Nicoletta ; Culot, Maurice ; Czech, Hermann ; D'Amato, Claudio ; D'Ardia, Giangiacomo ; Dardi, Costantino ; De Portzamparc, Christian ; Digerud, Jan ; Noto, Anna Di ; Dixon, Jeremy ; Eroli, Pierluigi ; Farina, Paolo ; Farrel, Terry ; Feugas, Jean-Pierre ; Friday ; Gardella, Ignazio ; Gasbarian, John Joseph ; Gehry, Frank ; Genovese, Federico ; gold, Michael ; Grashorn, Burkhard ; Graves, Michael ; Greenberg, Allan ; Grossi, Giuseppe ; Grumbach, Antoine ; Hilmer, Heinz ; Hollein, Hans ; Huet, Bernard ; Isozaki, Arata ; Helmut, Jahn ; Jan & Jon ; Johnson, Philip Cortelyou ; Jones, Edward ; Kijima, Yasufumi ; Kleihues, Joseph-Paul ; Koolhaas, Rem ; Krier, Leon ; Kupper, Eugene ; Lamunière, Jean-Marc ; Lepère, Yves ; Leroy, Bernard ; Loerakker, Ben ; Londberg, Jon ; Machado, Rodolfo ; Mack, Mark ; Mallas, Frank ; Mariotti, Roberto ; Martini, Massimo ; Matzkin, Donald ; Milani, Pino ; Minardi, Bruno ; Montes, Fernadno ; Montuori, Francesco ; Mooney, Kemp ; Moore, Charles ; mozuna, Monta ; Mulas, Franco ; Neumann, Gerd ; Pierluigi, Nicolin ; Nicolosi, Patrizia ; Oliver, Richard ; Patetta, Luciano ; Patrizi, Giampietro ; Pfeiffer, Herbert ; Pierluisi, Franco ; Placidi, Corrado ; Podrecca, Boris ; Portoghesi, Paolo ; Purini, Franco ; Rauch, John ; Reichlin, Bruno ; Reinhart, Fabio ; Ridolfi, Mario ; Rijnboutt, Kees ; Rosato, Enzo ; Rossi, Aldo ; Ruijssenaars, Hans
Samuel, Danny Marc ; Santelli, Serge ; Sattler, Christoph ; Scolari, Massimo ; Scott-Brown, Denise ; Silvetti, Jorge ; Slovic, David ; Gordon-Smith, Thomas ; Stern, Robert ; Architects, Taft ; T.A.U. (Théorie - Architecture - Urbanisme) ; Terry, Quinlan ; Tesar, Heinz ; Thermes, Laura ; Tigermann, Stanley ; Timme, Robert Howard ; Torre, Susanna ; Turnbull, William ; Tusquets, Oscar ; Ungers, Oswald Mathias ; Venezia, Francesca ; Venturi, Robert ; Van Kostelac, Ante Josip ; Wilson, Peter ; Wontroba, Werner Christian ; Zenghelis, Elia
Biennale di Venezia, 01.06 - 28.09.1980
Engels
Engels
kunstcatalogus